Perfil conceptual de equilibrio a partir de las ideas en comunidades culturalmente diferenciadas: implicaciones para una educación en ciencias en una sociedad culturalmente diversa - Pedreros Martínez, Rosa Inés (Revista Científica, 2011)
Since the early 80's research in science education have focused on the study of ideas, conceptions and representations of students. Studies in which questions still persist: ¿Why do not students learn about what they are taught? And ¿why not is achieved meaningful learning? Particularly in Colombia makes sense to take into mind the ideas that circulating because is made up culturally different communities, which implies an epistemological and cultural diversity. Thus, is formulated the research question; What are the relationship in the relevance and underlying epistemological and ontological commitments to the explanations about the balance in the science and in two culturally different communities? The research is part of the cultural theoretical perspective, intercultural, and multicultural knowledge settings, the aim is to determine the interrelationships between the relevance and commitment (epistemological and ontological).